Concordance between expected and observed bacilloscopy results of clinical forms of leprosy: a 6-year retrospective study in Recife, State of Pernambuco, Brazil - Ana Amélia Lucena Cavalcanti; Norma Lucena-Silva; Ulisses Ramos Montarroyos; Patrícia Maria Cavalcanti Carneiro de Albuquerque (Revista da Sociedade Brasileira de Medicina Tropical, 2012)
INTRODUCTION: Operational classification of leprosy based on the number of skin lesions was conceived to screen patients presenting severe forms of the disease to enable their reception of a more intense multidrug regimen without having to undergo lymph smear testing. We evaluated the concordance between operational classification and bacilloscopy to define multibacillary and paucibacillary leprosy. METHODS: We selected 1,213 records of individuals with leprosy, who were untreated (new cases) and admitted to a dermatology clinic in Recife, Brazil, from 2000 to 2005, and who underwent bacteriological examination at diagnosis for ratification of the operational classification. RESULTS: Compared to bacilloscopy, operational classification demonstrated 88.6% sensitivity, 76.9% specificity, a positive predictive value of 61.8%, and a negative predictive value of 94.1%, with 80% accuracy and a moderate kappa index. Among the bacilloscopy-negative cases, 23% had more than 5 skin lesions. Additionally, 11% of the bacilloscopy-positive cases had up to 5 lesions, which would have led to multibacillary cases being treated as paucibacillary leprosy if the operational classification had not been confirmed by bacilloscopy. CONCLUSIONS: Operational classification has limitations that are more obvious in borderline cases, suggesting that in these cases, lymph smear testing is advisable to enable the selection of true multibacillary cases for more intense treatment, thereby contributing to minimization of resistant strain selection and possible relapse.